Application of Finger Grasping Technique as Complementary Nursing Therapy in Elderly with Hypertension - Hibatullah, Fatih; Dewa Darma, Dimas; Fransisca, Dela (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Common chronic disease hypertension affects the elderly and, if untreated, may reduce their quality of life. Apart from drug therapy, safe and easy-to-manage supplementary treatments are needed. One alternative treatment for freezing is the finger grip approach, which is supposed to be soothing and lower blood pressure. This essay aims to employ knowledge of finger grip techniques as a supportive treatment option for elderly people with hypertension. Two senior persons diagnosed with hypertension are the subject of the approach's case study. Ten to fifteen minutes each day for three straight days was spent on the finger grip method. Measurements of blood pressure were taken both before and after the therapy. The systolic and diastolic blood pressure of both participants dropped following the finger grip treatment; they also stated they felt calmer and at ease. The conclusion of this case study is that the finger grip approach might be used as a supporting therapy to lower blood pressure in elderly patients with hypertension.